Investigating Efficient Thermal Distribution in a House Room by combining Statistics with Computational Fluid Dynamics: A theoretical investigation of an efficient thermal distribution in a house - Martins, Jairo Aparecido; Siqueira, Adriano Francisco; Romao, Estaner Claro (Engineering, Technology & Applied Science Research, 2024)
The study of energy sources is an open subject due to constraints on the current energy global production versus the current and future energy demands. From the consumption perspective, houses pull considerable energy from the electrical grid. With that being said, this paper investigates the theoretical thermal distribution of the heat in the basement of a house and measures the theoretical temperatures throughout different points at the same height by using statistics and numerical simulation. The numerical simulation, such as Computational Fluid Dynamic Analysis by COMSOLTM combined with Statistics by MiniTabTM was utilized to determine the most economical settings for the variables in the heating system evaluation. It is understood that thermal comfort for householders is achieved when the heat is evenly distributed in the room. To have a more realistic model set-up, the air flow in the room was considered as a turbulent model. The studied variables were intake airflow, positioning of the vents (intakes), airflow temperature, and external temperature. The results showed the significance of the variables. The latter were ranked from the highest to the lowest as: external temperature, airflow velocity, inlet location, and temperature input, while the highest interaction was found between the external temperature and air inlet velocity. This study comes up with a superior understanding of the system and generates an efficient setting for the variables for energy-saving purposes.